PENGARUH POSTER CARA MENYIKAT GIGI TERHADAP SKOR PLAK GIGI PADA ANAK USIA 6-12 TAHUN (Kajian di Panti Asuhan Brayat Pinuji dan Panti Asuhan Sancta Maria Kalibawang â Kulonprogo) - , MIRSA RENANING SUKMA; , drg. Hendrawati, M. Kes, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Plaque control is a main key in maintaining oral health that can be carried out either by brushing teeth. Brushing teeth is a part of daily routine that is easily accepted in oral hygiene practice. The age of 6 to 12 years old is an age period of permanent dentition so that the prevention of dental disease is really necessary to be performed. Poster is one of a visual educational media that helps to change a personâs behavior by increasing knowledge, accelerating capability and interest in behavior. Children aged 6 to 12 years old in a growth and development period will respond new things by developing their behaviors and skills. This study aimed to find out the effect of poster about how to brush teeth towards plaque score in children aged 6 to 12 years old. Subjects were 30 children of Brayat Pinuji and Sancta Maria Kalibawang- Kulonprogo orphanage aged 6 to 12 years old. Subjects performed brushing teeth while seeing poster posted in a bathroom wall for 21 days. Plaque score measurement used OâLeary method was carried out 4 times in day 0 (before poster being posted), day 7, day 14, and day 21. Plaque score data were then analyzed using repeated anova test. The result showed a significant difference (p<0,05) between plaque score mean before poster being posted (plaque score day 0) with plaque score mean after poster being posted (day 7, 14, and 21). In conclusion, poster about how to brush teeth has an effect in decreasing plaque score in children aged 6 to 12 years old.